2018
DOI: 10.1136/bmjopen-2017-017745
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence: a cross-sectional study among pregnant women in different regions of Sri Lanka

Abstract: ObjectivesThe aims of this study were to assess the regional differences in domestic violence among pregnant women in the capital district and in the tea plantation sector of Sri Lanka, to explore potential contributory factors and to assess whether healthcare workers addressed domestic violence and disclosure among survivors.DesignA cross-sectional study was carried out using interviewer-administered Abuse Assessment Screen.SettingFifty-seven antenatal clinic centres in the capital district and 30 in the tea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 2 publications
1
15
2
Order By: Relevance
“…However, low economic empowerment and dependency on men for income may have strapped them into a situation of tolerating IPV. Sri Lankan estate communities have been recorded with a high prevalence of IPV and gender based violence (Muzrif et al, 2018;Perera et al, 2011;Senanayake, Navaratnasingam, & Moonesinghe, 2008). In the present study, women residing in the estate sector have reported more justifying attitudes towards IPV compared to both rural and urban women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, low economic empowerment and dependency on men for income may have strapped them into a situation of tolerating IPV. Sri Lankan estate communities have been recorded with a high prevalence of IPV and gender based violence (Muzrif et al, 2018;Perera et al, 2011;Senanayake, Navaratnasingam, & Moonesinghe, 2008). In the present study, women residing in the estate sector have reported more justifying attitudes towards IPV compared to both rural and urban women.…”
Section: Discussionmentioning
confidence: 99%
“…Among the global burden of disease (GBD) regions, highest IPV prevalence reported from Central sub-Saharan Africa (65.6%), whereas the South-East Asian region has reported a prevalence of 28.0% (WHO, 2013). As a country in the South-East Asian region, IPV prevalence of Sri Lanka varies between 18.3% and 60% with a recent study indicating 38.6% being abused during their lifetime and 15.9% being abused during the past 12 months (Muzrif, Perera, Wijewardena, Schei, & Swahnberg, 2018;Perera, Gunawardane, & Jayasuriya, 2011). The reported high prevalence of IPV and the wide range of health, social and economic ISSN: 2581-3358 Available online at Journals.…”
Section: Introductionmentioning
confidence: 99%
“…During both pregnancy and the postpartum period , six studies investigated associated factors with IPV ( 39 , 45 , 60 , 61 , 90 , 94 ). Victim-related factors at the individual level included history of IPV ( 39 , 61 , 90 ), women who have lower education ( 90 ), and women reporting regular alcohol use during pregnancy and puerperium ( 94 ). One study reported higher risk of IPV for employed women ( 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…At the family level , longer duration of marriage ( 39 ), and insufficient income ( 45 , 60 , 90 ) constituted risk factors (see Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In Iran, the prevalence of DV against pregnant women is 28.2% [12]. A cross-sectional study on 2088 Sri Lankan pregnant women reported that the prevalence of DV was 15.9% [13]. In Changsha City, China, Zhang et al reported that 11.3% of women had experienced DV during pregnancy [1].…”
Section: Introductionmentioning
confidence: 99%